PERBANDINGAN EFISIENSI TEBAL PERKERASAN LENTUR MENGGUNAKAN METODE MAK 1987 DAN MDPJ 2017 PADA RUAS JALAN TINGKARANG-MUARO SUNGAI LOLO KECAMATAN MAPAT TUNGGUL SELATAN, KABUPATEN PASAMAN - Zenata Putri; Helga Yermadona; Yorizal Putra (Progressive : Journal of Advanced Engineering and Technology, 2026)
Pasaman Regency is a district in West Sumatra Province which is located in Lubuk Sikaping, one of the existing sub-districts, namely Mapat Tunggul Selatan District with an area of 471.72 km2. Judging from the road conditions which are far from decent, it makes it difficult for the community to carry out social and economic activities, therefore the solution to this problem is to plan a flexible pavement thickness. +000 8+000 with a road width of 4.5 m. before doing the calculations, first find out the CBR of the soil, the planned age, and daily traffic data. Then the calculations use the 1987 MAK and MDPJ 2017 methods. The calculation results use the 1987 Highways Component Analysis method, namely Laston 7.5 cm, Top Foundation layer 20 cm and the Lower Foundation Layer 10 cm, while the 2017 road pavement design manual namely AC WC 4 cm, AC BC 6 cm, and LPA class A class 40 cm. For the 1987 Bina Marga 1987 component analysis method, the Budget Plan (RAB) obtained Rp.19.491.720.949 and the 2017 Road Pavement Design Manual Method, the price you get is Rp. 24.911.239.684.Keywords: Flexible Pavement, 1987 Bina Marga Component Analysis Method, 2017 Road Pavement Design Manual Method, RAB